Corpus callosum tissue loss and development of motor and global cognitive impairment: the LADIS study - Frederiksen, Kristian Steen; Garde, Ellen; Skimminge, Arnold; Barkhof, Frederik; Scheltens, Philip; Straaten, Elisabeth C. W. van; Fazekas, Franz; Bäzner, Hansjörg; Verdelho, Ana; Ferro, José M.; Erkinjuntti, Timo; Jokinen, Hanna; et al. (Dementia and geriatric cognitive disorders, 2012)
Objective: To examine the impact of corpus callosum (CC) tissue loss on the development of global cognitive and motor impairment in the elderly. Methods: This study was based on the Leukoaraiosis and Disability (LADIS) study. Assessment of cognitive and motor functions and magnetic resonance imaging (MRI) were done at baseline and at a 3-year follow-up in nondemented elderly subjects. Results: 328 of 639 LADIS subjects had MRIs at baseline and at the 3-year follow-up, which allowed for assessment of CC. Logistic regression revealed differential tissue loss rates in posterior CC in subjects converting to dementia, compared to nonconverters (p < 0.05). Anterior and posterior CC tissue loss was significantly correlated with self-perceived memory impairment in nonconverters (p < 0.05). CC tissue loss was also significantly associated with impaired single leg stance time (p < 0.01). Conclusion: The present longitudinal study on CC supports the role of callosal tissue loss in the development of global cognitive as well as motor impairment.
Gesehen am 22.05.2023
Erscheinungsjahr im PDF in der Kopf- und Fußzeile: Dement Geriatr Cogn Disord 2011;32:279–286, Urheberrecht: 2012 S. Karger AG, Basel ; Erscheinungsjahr auf der Frontdoor: Dement Geriatr Cogn Disord (2012) 32 (4): 279–286, online veröffentlicht:Januar 19 2012